Research into attitudes of subjects of education process in teaching programming - Abylkassymova, Alma; Mukasheva, Manargul; Zhumagulova, Zaure (Opción, 2019)
The article presents some outcomes of probing into attitudes and needs of subjects of the education process in teaching programming at school via a set of complementary research methods like theoretical, comparative and questionnaire survey methods. As a result, the majority of female respondents favored the programming skills exactly in terms of brain building. Teachers and IT (Information Technology) specialists would regard the Scratch facility as the most suitable tool to teach programming at primary school, Python as applicable for middle school, and C as applicable for the senior level of a secondary school for designing software.